Fintech development, corporate tax avoidance and firm value - Tang, M.; Hu, Y.; Hou, Y.; Oxley, Leslie; Goodell, J.W. (2025)
We examine the relationship between fintech development and tax avoidance, as well as investigate whether this relationship has an impact on firm value. Using the data from Chinese A-listed firms, we provide evidence that fintech development increases tax avoidance, which facilitates firm value. Moreover, we find that fintech raises after-tax income and future cash flow by facilitating firms to avoid tax. Fintech development is negatively associated with tax risk and positively related to the effectiveness of firms in capitalizing on tax preferences. We further determine that the positive effects of fintech are more pronounced among firms with low internal information quality, weak internal control, and more geographically dispersed operations. Digital transformation, cash flow uncertainty, and regional economic development are the important potential channels through which fintech development influences tax avoidance. Our results are robust to alternative measures and endogeneity issues.